2022
DOI: 10.1186/s13027-022-00433-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of platinum monotherapy with concurrent chemoradiation therapy versus platinum-based dual drug therapy with concurrent chemoradiation therapy for locally advanced cervical cancer: a systematic review and meta-analysis

Abstract: Objective To compare the survival outcomes and adverse events of patients with locally advanced cervical cancer (LACC) who received platinum monotherapy with concurrent chemoradiation therapy (CCRT) versus platinum-based dual drug therapy with CCRT. Method All relevant literature was screened form the PubMed, EMBASE, Web of Science, The Cochrane Library and other databases from their establishment to October 2020. The main endpoint indicators inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Therefore, PTX is often administered concurrently with radiotherapy to exert a synergistic anti-tumor effect, which however may aggravate the damage to normal tissues caused by radiotherapy. Clinical cases (Zhang et al, 2007;Dai et al, 2011) as well as our study have shown that PTX can aggravate RIPF, the damage to normal lung tissue from thoracic irradiation. In light of the observation that ERK is the main signaling pathway that promotes FBs activating into more vigorous myofibroblasts (Foglia et al, 2019;Ng et al, 2019;Wu et al, 2020), and that PTX can up-regulate ERK activity (Seidman et al, 2001;Huang et al, 2019a), also with the findings that overexpression of Spry2 can abolish PTX-induced c-Raf activation (Ahn et al, 2010), we explored the mechanism by which PTX aggravates RIPF.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, PTX is often administered concurrently with radiotherapy to exert a synergistic anti-tumor effect, which however may aggravate the damage to normal tissues caused by radiotherapy. Clinical cases (Zhang et al, 2007;Dai et al, 2011) as well as our study have shown that PTX can aggravate RIPF, the damage to normal lung tissue from thoracic irradiation. In light of the observation that ERK is the main signaling pathway that promotes FBs activating into more vigorous myofibroblasts (Foglia et al, 2019;Ng et al, 2019;Wu et al, 2020), and that PTX can up-regulate ERK activity (Seidman et al, 2001;Huang et al, 2019a), also with the findings that overexpression of Spry2 can abolish PTX-induced c-Raf activation (Ahn et al, 2010), we explored the mechanism by which PTX aggravates RIPF.…”
Section: Discussionsupporting
confidence: 70%
“…Therefore, in clinical practice, it is extremely important to select the appropriate chemotherapy scheme in accordance with the patient’s actual tolerance. Therefore, the choice of LACC treatment remains a huge problem in the currently available treatment - modalities ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…For those patients not tolerating cisplatin chemotherapy, carboplatin can be a good substitute [ 8 ]; an alternative regimen among those patients intolerant of cisplatin is a combination of cisplatin plus fluorouracil given every three to four weeks can be considered [ 8 , 9 ]. The role of a combination of cisplatin plus gemcitabine is still evolving [ 10 , 11 ]. The role of targeted therapy and precision therapy/radiobiotherapy in the future needs to be defined and likely to improve the outcomes [ 12 , 13 ].…”
Section: Methodsmentioning
confidence: 99%